Cucu Nabi Muhammad Menikah dengan Orang Makassar : Studi Pernikahan Perempuan Islam Sayyid di Cikoang, Takalar - Mustika Sari Wulandari; Abdul Rahman; Ahmadin Ahmadin; Rifal Rifal (IAIN Syekh Nurjati Cirebon, 2019)
Abstract This article discusses the marriage of Muslim woman Sayyid in Cikoang, Takalar, South Sulawesi. Sayyid Islam is believed to have originated from the Prophet's grandson, Muhammad, who believed that he could only marry Sayyid's own Muslims. The study focused on women who married people outside of Sayyid. For this purpose, this article discusses (1) the background to a woman of Sayyid descent so that she chooses to marry a non-Sayyid man by reason of their own choice and for liking each other with her partner (2) the way of the descendants of Sayyid girls carry out their marriages with non-Sayyid men have differences with the processes commonly carried out by the community in general, the difference in the marriage process is not running a series of processes carried out before the wedding day which is usually done by the Makassar people (3) The marriage was also not attended and not witnessed by the family of the Sayyid woman. As for the relationship between Sayyid's daughter and her family, it can be said that she has broken up or has no family ties, even the daughter has been considered dead by her family since she chose to marry a non-Sayyid man, as well as the relationship between her husband and children towards the family the great Sayyid woman.Keywords: Sayyid Islam, Marriage, Anthropology of Religion.